Dopamine inhibits the expression of proinflammatory cytokines of microglial cells through the formation of dopamine quinone in the mouse striatum - Yasuhiro Yoshioka; Yuta Sugino; Akiko Yamamuro; Yuki Ishimaru; Sadaaki Maeda (Elsevier, 2022)
We previously reported that dopamine (DA) attenuated lipopolysaccharide (LPS)-induced expression of proinflammatory cytokines through the formation of DA quinone (DAQ) in murine microglial cell line BV-2 and primary murine microglial cells. To reveal whether DA inhibits the expression of proinflammatory cytokines of microglial cells through the formation of DAQ in the central nervous system (CNS), in this study, we examined the effect of DAQ on LPS-induced mRNA expression of proinflammatory cytokines in C57BL/6 mouse brain under two experimental conditions: 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) administration and l-dopa/carbidopa administration. Acute MPTP administration reduced the number of tyrosine hydroxylase-positive cells in the substantia nigra, and decreased the level of quinoprotein, an indicator of DAQ formation, in the striatum. Real-time RT-PCR analysis revealed that intraperitoneal administration of LPS increased the mRNA levels of proinflammatory cytokines, including tumor-necrosis factor-α and interleukin-1β, in the striatum. These increases were enhanced in MPTP-treated mice. On the other hand, l-dopa/carbidopa administration increased the level of quinoprotein, attenuated the LPS-induced mRNA expression of proinflammatory cytokines, and reduced the LPS-induced increase in the number of microglial cells in the striatum. These results suggest that DA attenuate the expression of proinflammatory cytokines in microglia through the formation of DAQ in the CNS.